AB0356 How Does First-Line Abatacept Compare To Other Biologics? Data from A Rheumatic Disease Registry. (15th July 2016) - Michaud, K.; Pedro, S.; Simon, T.; Wolfe, F.
Abstract : Background: Observational studies are critical in assessing medication safety and effectiveness in the real world. Non-random assignment can provide insight to how and when medications are prescribed. Since the US introduction of TNF inhibitors (TNFi) in 1998, several newer biologics with varying mechanisms of action are available to patients and physicians. Most physicians prescribe TNFi prior to another biologic, however this trend may be changing. Objectives: To compare the characteristics and outcomes (serious infections and malignancies) of patients who receive abatacept (ABA) vs TNFi as a first biologic. Methods: Participating patients with RA in the National Data Bank for Rheumatic Diseases (NDB) provided treatment and other characteristics (sociodemographics and comorbidities) through self-reported biannual questionnaires. Only responses from 2005–2014 were used for greater comparability. Initiators of biologics were stratified by type (ABA vs. TNFi) and by number of previously exposed biologics. All patient-reported outcomes were verified by medical record review except non-melanoma skin cancer. Patients who had an outcome in the 180 days before treatment initiation were excluded from the analysis for that outcome. Marginal structural models were used to estimate the effect of treatment on the outcome by an appropriate control for the effects of time-dependent confounders using stabilized weights. Variables included sex, employment, marital status, smoking, education, income, select comorbidities, and medications prescribed. These results are reported as adjusted hazard ratios (HR). We repeated the analysis comparing ABA with all other biologics. Results: A total of 3, 088 RA patients initiated a first biologic during the study. Of these, 348 received ABA without any prior biologics, having a mean (median) time in the study of 2.6 (1.9) years with a total of 900 patient-years of follow-up. For patients who initiated a TNFi, 3.4 (2.4) years was the mean (median) time in the study with a follow-up of 9296 patient-years. The ABA patients were older, smoked more, and used more prednisone and less MTX compared to those starting their first non-ABA biologic. They also tended to have worse disease activity measured by HAQ and PAS. The crude and adjusted HR of hospitalized infections were: 0.7 (0.2–2.3) and 0.5 (0.2–1.6) and for all malignancies: 1.5 (0.84–2.8) and 1.1 (0.7–2.0), respectively. The results were similar when compared to all biologics (N=2, 900). The table shows baseline characteristics comparing Abatacept and TNFi initiators. Conclusions: In this RA cohort receiving a first biologic therapy, there appears to be a trend of channeling with ABA. Patients starting ABA tended to be older and have worse disease outcomes. Despite the baseline differences, there was no difference in hospitalized infections and cancers between the groups. This was still true when the comparison was made between ABA and other biologic initiators. Disclosure of Interest: None declared